Hubungan Kandungan Hara Tanah dan Produksi Gambir di Sumatera Barat - Kurnia Dewi Sasmita; Bambang Eka Tjahjana (Pusat Penelitian dan Pengembangan Perkebunan, 2011)
Gambier (Uncaria gambir Roxb.) is a useful plant, especially for for the pharmaceutical industry. Productivity of gambier is still low because one of them caused by low soil fertility in cropping areas gambier. This study aimed to determine the relationship of soil nutrient content, nutrient content of plant and crop production of gambier at the one of production centers in West Sumatra for the basis of determined fertilizer needs of gambier. The experiment was conducted with a random sampling method on the plot owned by farmers in the Kampung Koto Marapat, West Sumatra.The results showed that each ton of dry leaves of gambier will take the nutrients of 19.8 kg N, 1.3 kg P and 13.6 kg K. High yield crops need nutrients at 452 kg N / ha, 30 kg P / ha and 296 kg K / ha with population 2500 plants / ha. The high production of gambier is not indicated significantly by high levels of NPK nutrients in leaf and high soil nutrient levels. Low pH was one factor limiting the production of gambier.